124k views
1 vote
What do you do after you multiply an equation in the elimination method?2x -3y=-11x+3y = 8

User Amaseuk
by
5.2k points

1 Answer

1 vote

1) Let's multiply the second equation by -2, to eliminate x

2x -3y=-11

x+3y = 8

2) Now let's add both equations

2x -3y=-11

-2x-6y = -16

--------------------

-9y = -27

3) Divide both by -9

y=3

4) Plug y=3 into the simpler original equation, to make calculations easier:

x +3y=8

x+3(3) =8

x +9 =8 Subtract 9 from both sides

x = 8-9

x=-1

So, after multiplying it we add both equations to eliminate one variable either x or y.

User Tvaroh
by
4.8k points